EFFICIENCY MEASUREMENT WITH INDUSTRY-BASED DATA ENVELOPMENT ANALYSIS (DEA): A LITERATURE REVIEW - Silvia Rahmadani; Nurmala Ahmar; JMV Mulyadi (Sean Institute, 2023)
This research describes efficiency measurement with Industry-based Data Envelopment Analysis (DEA). The samples obtained amounted to 25 articles that discussed Data Envelopment Analysis (DEA). Researchers classify based on researchers, titles, input and output variables, and the results of each article. The research design used in this research is Literature Review. Based on the results of a review of several articles regarding efficiency measurement with Data Envelopment Analysis, it is as follows, the ability to produce maximum output with existing inputs is the expected performance. When measuring Data Envelopment Analysis (DEA) we are faced with the condition of how to get the optimal output level with the existing input level, or determine the minimum input level by shouting a certain output level.